R&D expenditures: Accounting choices and market price reactions - Abdul Latif, Rohaida; Taufil Mohd, Kamarun Nisham; Abu Bakar, Robiah; Wan Hussin, Wan Nordin; Ku Ismail, Ku Nor Izah (Universiti Utara Malaysia, 2005)
This paper examines the value relevance of R&D reporting among public listed companies in Malaysia for the years 2000 and 2001, subsequent to the introduction of FRS 109, Accounting for Research and Development (formerly known as MASB 4).FRS 109 states that a firm should expense its research costs and could capitalize the development cost if the latter is expected to bring future benefits.Otherwise, the development expenditure is to be expensed.Test results based on Ohlson’s (1995) valuation model shows that for capitalizers, the amount of R&D expenditure, either expensed or capitalized, influences the stock prices positively.As for the expensers, even though the amount expensed influences stock prices, this relationship is driven by outliers; when we dropped the outliers, the result is no longer significant.These results indicate that R&D activities of capitalizers are expected to bring future benefits and consequently lead to higher prices while the R&D activities of expensers are more difficult to evaluate given a small sample size and the presence of outliers.